(E)-3-(4-Decyloxyphenyl)-1-(2-hydroxyphenyl) prop-2-en-1-one - Zainab, Ngaini; Norashikin Irdawaty, Abd Rahman; Hasnain, Hussain; Ibrahim, Abdul Razak; Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C 25 H 32 O 3, the enone group is in an s-cis configuration. The dihedral angle between the benzene rings is 8.84 (7). An intramolecular OH... O interaction between the keto and hydroxy groups forms an S (6) ring motif. Intermolecular CH... O interactions link the molecules into supramolecular chains along the c axis which are subsequently stacked down the b axis; the crystal structure is further consolidated by CH...[pi] interactions.